Implementasi Komunikasi Interpersonal Kepala Sekolah dengan Guru dalam Meningkatkan Kinerja di Madrasah Ibtidaiyah Negeri 2 Tanjung Balai - Abidin, Syahrul; Saragih, Yoserizal; Sihombing, Haris Fadillah (ARZUSIN, 2023)
This research to find out how the implementation of interpersonal communication between school principals and teachers improves performance. The theory that I use to discuss or explore this research is Bureaucracy Theory. The method used in this research is a qualitative descriptive method with the research informants used in this research being the principal and teachers at Madrasah Ibtidaiyah Negeri 2 Tanjung Balai who are related to the research problem that the principal will discuss with teachers in improving performance. The results of the research found that the implementation of interpersonal communication between principals and teachers in improving performance involves effective interpersonal communication used by principals in paying attention to teachers' performance. However, not only by using effective communication, but also by having the principal continue to control or provide motivation to teachers to support improving teacher performance well.